Public policy analysis : - Dunn, William N (Prentice-Hall, 1981)
This book introduces students to the process and methodology of public policy analysis. Using a problems-oriented and a multidisciplinary synthesis approach, this text bridges the gap between theory and practice. The text draws from political science, public administration, economics, decision analysis, and social and political theory to achieve the only integrated, multidisciplinary text on policy analysis currently available.